2015
DOI: 10.1002/bit.25666
|View full text |Cite
|
Sign up to set email alerts
|

A novelin situgas stripping‐pervaporation process integrated with acetone‐butanol‐ethanol fermentation for hyper n‐butanol production

Abstract: Butanol is considered as an advanced biofuel, the development of which is restricted by the intensive energy consumption of product recovery. A novel two-stage gas stripping-pervaporation process integrated with acetone-butanol-ethanol (ABE) fermentation was developed for butanol recovery, with gas stripping as the first-stage and pervaporation as the second-stage using the carbon nanotubes (CNTs) filled polydimethylsiloxane (PDMS) mixed matrix membrane (MMM). Compared to batch fermentation without butanol rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 48 publications
(75 reference statements)
1
86
0
Order By: Relevance
“…In general, the tradeoff between water consumption and butanol concentration is valuable for microbial butanol production from lignocellulosic biomass. The improved butanol concentration significantly contributes to the reduced product recovery cost by conventional distillation [20, 33]. In consideration of butanol concentration, more water is preferable for providing a suitable environment for fermentation strain by completely removing inhibitory products and residual NaOH.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the tradeoff between water consumption and butanol concentration is valuable for microbial butanol production from lignocellulosic biomass. The improved butanol concentration significantly contributes to the reduced product recovery cost by conventional distillation [20, 33]. In consideration of butanol concentration, more water is preferable for providing a suitable environment for fermentation strain by completely removing inhibitory products and residual NaOH.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past three decades, extensive research were carried out to find solutions for overcoming Clostridia strain degeneration. It was reported that addition of sodium acetate to MP2 medium could prevent degeneration in Clostridium beijerinckii NCIMB 8052 and BA101, a solvent-hyperproducing mutant derived from 80524; Recently, in hyper-butanol producing C. acetobutylicum JB200, the integrated gas stripping to remove product during fermentation was found to increase butanol productivity without culture degeneration56.…”
mentioning
confidence: 99%
“…Gas stripping is an established product recovery technique for ABE separation [23, 4851]. It was confirmed that ethanol intolerance was one of the reasons of growth inhibition.…”
Section: Discussionmentioning
confidence: 99%